2017
DOI: 10.3892/ijmm.2017.2880
|View full text |Cite|
|
Sign up to set email alerts
|

Isopsoralen-mediated suppression of bone marrow adiposity and attenuation of the adipogenic commitment of bone marrow-derived mesenchymal stem cells

Abstract: Osteoporosis (OP) increases the risk of bone fractures and other complications, and is thus a major clinical problem. In this study, we examined the effect of isopsoralen on the differentiation of bone-derived marrow mesenchymal stem cells (BMSCs) into osteoblasts and adipocytes, as well as bone formation under osteoporotic conditions. Primary femoral BMSCs isolated from C57BL/6 mice were used to evaluate the isopsoralen-mediated regulation of the expression of alkaline phosphatase (ALP), osteocalcin (OCN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…However, in a recent paper, Ge et al (2019) had demonstrated that angelicin was able to not only increase the proliferation of osteoblast but also to induce the expression of alkaline phosphatase (ALP) after 7 days of treatment while the matrix mineralization of the cells can be seen on the 12 th day of treatment with angelicin. Similar observation of increased cell proliferation, ALP activity and mineralization of osteoblasts by angelicin were reported in MC3T3-E1 (mouse osteoblast precursor) cells and primary bone marrow mesenchymal stem cells (BMSC) with the exception that BMSC cells did not experience any changes in cell proliferation (Wang et al, 2017b;Ge et al, 2018).…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 76%
See 4 more Smart Citations
“…However, in a recent paper, Ge et al (2019) had demonstrated that angelicin was able to not only increase the proliferation of osteoblast but also to induce the expression of alkaline phosphatase (ALP) after 7 days of treatment while the matrix mineralization of the cells can be seen on the 12 th day of treatment with angelicin. Similar observation of increased cell proliferation, ALP activity and mineralization of osteoblasts by angelicin were reported in MC3T3-E1 (mouse osteoblast precursor) cells and primary bone marrow mesenchymal stem cells (BMSC) with the exception that BMSC cells did not experience any changes in cell proliferation (Wang et al, 2017b;Ge et al, 2018).…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 76%
“…In addition, two markers from the mTOR complex 1 (mTORC1) signaling pathway, p-S6 and p-4EBP1, were analyzed in both osteogenic and adipogenic conditions. When comparing the two markers, p-S6 showed marked downregulation in expression while p-4EBP1 was upregulated under both differentiation conditions for 7 and 14 days (Wang et al, 2017b). mTOR is a conserved pathway that plays a role in regulating cell growth and metabolism and it had been reported that mTORC1 participates in adipogenesis (Polak et al, 2008;Betz and Hall, 2013).…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancermentioning
confidence: 95%
See 3 more Smart Citations